2017
DOI: 10.2119/molmed.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin-6 Preserves R-spondin-1 Expression and increases Resistance of intestinal Epithelium to injury in Mice

Abstract: Sirtuin-6 (Sirt6) is a critical epigenetic regulator, but its function in the gut is unknown. Here, we studied the role of intestinal epithelial Sirt6 in colitis-associated intestinal epithelial injury. We found that Sirt6, which is predominantly expressed in epithelial cells in intestinal crypts, is decreased in colitis in both mice and humans. Colitis-derived inflammatory mediators including interferon-γ and reactive oxygen species strongly inhibited Sirt6 protein expression in young adult mouse colonocyte (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Both SIRTs have been shown to regulate inflammation in the gut (Akimova et al, 2014;Lo Sasso et al, 2014;Wellman et al, 2017;Zhang et al, 2018). We found that compared with fetal EDMs, aged EDMs expressed less SIRT1 and 6 ( Fig 3B-Left, Middle), consistent with the previous observations of their decline in the aged gut (Liu et al, 2017a;Igarashi et al, 2019). Because age-associated changes in gut microbiome composition is correlated with increases in the pro-inflammatory marker serum monocyte chemoattractant protein (MCP-1) (Conley et al, 2016), which in turn has been implicated in aging-related macrophage dysfunction (Thevaranjan et al, 2017), we analyzed this cytokine in the aged EDMs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Both SIRTs have been shown to regulate inflammation in the gut (Akimova et al, 2014;Lo Sasso et al, 2014;Wellman et al, 2017;Zhang et al, 2018). We found that compared with fetal EDMs, aged EDMs expressed less SIRT1 and 6 ( Fig 3B-Left, Middle), consistent with the previous observations of their decline in the aged gut (Liu et al, 2017a;Igarashi et al, 2019). Because age-associated changes in gut microbiome composition is correlated with increases in the pro-inflammatory marker serum monocyte chemoattractant protein (MCP-1) (Conley et al, 2016), which in turn has been implicated in aging-related macrophage dysfunction (Thevaranjan et al, 2017), we analyzed this cytokine in the aged EDMs.…”
Section: Resultssupporting
confidence: 90%
“…A compromised gut barrier allows microbes and unwanted antigens to cross the epithelium and generate inflammation (systemic endotoxemia), which may contribute to a variety of diseases, ranging from metabolic syndrome and chronic organ dysfunctions to neurodegenerative diseases and cancers (Yacyshyn et al, 1996;Barbara, 2006;Camilleri & Gorman, 2007;Sandek et al, 2007Sandek et al, , 2008Sandek et al, , 2012Alam et al, 2014;Bischoff et al, 2014;Nouri et al, 2014;Samsam et al, 2014;van De Sande et al, 2014;Clairembault et al, 2015;Lee et al, 2015;Buscarinu et al, 2016;Xue et al, 2016;Ghosh, 2017). Evidence also shows that aging-related genes, that is, the sirtuins (SIRTs1, 3, 6), are critical for the integrity of the gut barrier and for controlling inflammation in the gut (Akimova et al, 2014;Akbulut et al, 2015;Liu et al, 2017b;Zhang et al, 2018). Despite the traction and the discovery of plausible targets to strengthen the barrier, for example, myosin light-chain kinase (Cunningham & Turner, 2012), our knowledge of the underlying mechanism(s) that reinforce the barrier when faced with stressors is incomplete, and practical strategies for pharmacologic modulation of the gut barrier remains unrealized.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT6 is involved in multiple essential biological processes, including genomic stability, inflammation and metabolism, and SIRT6 deficiency, leading to severe colitis in mice and increasing susceptibility to injurious insults in cells, and its overexpression enhances resistance to stress [ 5 , 23 ]. However, whether SIRT6 overexpression prevents colitis has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…FY Liu reported that intestinal epithelial cell-specific knockout of SIRT6 increases susceptibility to dextran sulfate sodium salt (DSS)-induced colitis in mice. Moreover, there is a decreased expression of colonic SIRT6 in both DSS-induced colitis mouse model and ulcerative colitis patients [ 5 ]. However, the effects of overexpressed SIRT6 on the colon have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In gut inflammation, colitis is associated with decreased levels of intestinal SIRT6. SIRT6 may plays a protection role by preserving the expression of R‐spondin 1 (Rspo1), an important trophic factor for intestinal epithelial cell growth 149 . In the dextran sulfate sodium‐induced colitis model, SIRT6 overexpression suppresses the activated NF‐κB and c‐Jun signaling, thereby alleviating the colitis in terms of clinical manifestations, histopathological damage, loss of tight junction function, and imbalanced intestinal microenvironment 150 .…”
Section: Human Diseasesmentioning
confidence: 99%